2017
DOI: 10.6060/mhc170188n
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics, Redox Processes, and Electronic Structures of Ferrocenyl-Containing BODIPYs, aza-BODIPYs, BOPHYs, Transition-Metal Dipyrromethenes and aza-Dipyrromethenes

Abstract: General trends in the UVКлючевые слова: BODIPY, аза-BODIPY, ферроцен, дипиррометен, аза-дипиррометен, фотофизика, окисли-тельно-восстановительные свойства.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…As it has been discussed previously, the presence of polarizable and electron-rich extended π-system in light-harvesting chromophore can facilitate noncovalent π–π interactions between such molecules and nanocarbon electron-acceptor materials. We have investigated potential noncovalent complex formation between pyrene–BODIPYs 2 – 4 and selected nanocarbon materials (C 60 and C 70 fullerenes, (6,5)-SWCNT, and graphene) using UV–vis and steady-state fluorescence approaches.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As it has been discussed previously, the presence of polarizable and electron-rich extended π-system in light-harvesting chromophore can facilitate noncovalent π–π interactions between such molecules and nanocarbon electron-acceptor materials. We have investigated potential noncovalent complex formation between pyrene–BODIPYs 2 – 4 and selected nanocarbon materials (C 60 and C 70 fullerenes, (6,5)-SWCNT, and graphene) using UV–vis and steady-state fluorescence approaches.…”
Section: Resultsmentioning
confidence: 92%
“…Design of new chromophores that are capable of harvesting sunlight in the low-energy visible and near-infrared (NIR) spectral envelopes attracted a lot of attention in recent decades because of the potential use of such systems in organic- and dye-sensitized solar cells. In addition, the ability to facilitate relatively strong noncovalent interactions between such chromophores and nanocarbon-based electron-accepting materials (fullerenes, nanotubes, and graphene) is thought to be advantageous in the processing of high-efficiency organic bulk heterojunction solar cells. To achieve this goal, many porphyrins, subphthalocyanines, and boron-dipyrromethenes (BODIPYs) were functionalized with a variety of electron-donating groups that improve donor–acceptor (D–A) interactions between extended π-systems. Alternatively, the introduction of the polyaromatic fragments that are either conjugated or not conjugated into chromophores’ π-system can also improve noncovalent interactions in these D–A assemblies. Covalently bound pyrene was shown to facilitate noncovalent interactions with carbon nanotubes and graphene. It has also been shown that when pyrene fragments are decoupled from the chromophores’ π-system, this extended aromatic group can facilitate an unwanted pyrene-to-chromophore electron-transfer process as well as the formation of a chromophore-centered triplet state. We have recently demonstrat...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of aza-BODIPYs and ferrocene is more and more examined in the literature due to the ability of aza-BODIPYs to be reduced at less negative potentials than their BODIPY analogues [75][76][77][78][79][80][81]. Aza-BODIPYs can also be reduced selectively in a one-electron process, providing new products displaying an absorption band beyond 800 nm.…”
Section: Bdp-42 (70000 L Molmentioning
confidence: 99%
“…The DFT calculations performed on IV (Figure ) predict the HOMO to be predominately centered on the BDP core's π system, while the LUMO of IV is predicted to be a π* orbital that occupies the BDP core with the characteristic orbital placement on the meso carbon , . Interestingly, this system is distinct in two ways: 1) the entire π system is not involved in the HOMO and LUMO orbitals on account of the warping, and 2) the frontier molecular orbitals of IV do not involve contributions from the metal center as they do in some ferrocene and cobalt‐based systems …”
Section: Resultsmentioning
confidence: 99%